Preparing Future Generations: The Importance of Elementary School Students' Technology Adaptation in an Era of Change - Ridha, Salwa Hikmatu; Rohiman, Isna Soffi Aristin; Setiani, Endang Selly; Giwangsa, Sendi Fauzi (Universitas Trunojoyo Madura, 2024)
This study aims to analyze the technological adaptability of elementary school students at SD Muhammadiyah Ciwahang in preparation for the challenges of the digital era. The approach used was qualitative, with a case study method involving students, teachers, and parents as research subjects. Data were collected through interviews, observations, and literature studies and then analyzed using the Miles and Huberman model, which includes data collection, reduction, data presentation, and conclusion drawing. The results showed variations in technology adaptability based on student age, device availability, and parental support. Lower-grade students tend to use technology for entertainment, while higher-grade students understand its benefits for learning. The main obstacles are limited infrastructure and digital literacy. Teachers play an important role in the integration of technology in learning, while parents contribute through supervision and guidance at home. This research recommends collaboration between schools, families, and the government to provide adequate facilities and improve students' technological competencies to support their future readiness.